5z-3=-19+9z

Simple and best practice solution for 5z-3=-19+9z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-3=-19+9z equation:


Simplifying
5z + -3 = -19 + 9z

Reorder the terms:
-3 + 5z = -19 + 9z

Solving
-3 + 5z = -19 + 9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9z' to each side of the equation.
-3 + 5z + -9z = -19 + 9z + -9z

Combine like terms: 5z + -9z = -4z
-3 + -4z = -19 + 9z + -9z

Combine like terms: 9z + -9z = 0
-3 + -4z = -19 + 0
-3 + -4z = -19

Add '3' to each side of the equation.
-3 + 3 + -4z = -19 + 3

Combine like terms: -3 + 3 = 0
0 + -4z = -19 + 3
-4z = -19 + 3

Combine like terms: -19 + 3 = -16
-4z = -16

Divide each side by '-4'.
z = 4

Simplifying
z = 4

See similar equations:

| 2y=5x-10forx | | 6t+3(5t-4)=12(2t)-5 | | x^2-2x=-15 | | 6(2k+1)-21=21 | | 1/3(n+1)=1/(3-5) | | y=(4y^2-x^2)/(4xy) | | 9-1a=5.66-1a | | Ln(12x)-ln(3)=5 | | 111y=37 | | K=3+5-2+6-(-5) | | 11=2-3v | | 85=.5x(17) | | 15m-4(2m-6)=38 | | 3*3*3-(31-2*3)= | | -2(3-7x)=22 | | 15-7(x-2)=1 | | (2sin2x)/x | | u^2-32u+31=0 | | 10x+9(3)=8 | | 1/4d_ | | f(x)=ln(81sin^2x) | | 3+4x=13+9x | | 2a^3b^0/c^2)-3 | | An=n^2+3n | | Tan^2x-5tanx-6=0 | | 2y=-3x+8 | | -4(7x+1)=-312 | | -5=-20+-25 | | 12x^2-132x+252=0 | | 30=7+N-4+8 | | 40=-2(23-y)+3(y-3) | | -8=17+6z |

Equations solver categories